The Effect of National Income, Exchange Rates, Foreign Exchange Reserves, and Inflation on Capital Goods Imports in Indonesia - Widiya, Heni; Hwihanus, Hwihanus; Riyadi, Slamet (Multiverse: Open Multidisciplinary Journal, 2023)
Capital goods are man-made products that play a crucial role in the production of commodities or services. This study conducts a comprehensive analysis, both in the long-term and short-term, to examine the influence of national income, exchange rates, foreign exchange reserves, and inflation on capital imports. Utilizing secondary data in the form of time series from Bank Indonesia and BPS (Central Statistics Agency) spanning from Q1 2005 to Q4 2020, the research employs the Error Correction Model (ECM) analysis technique. The findings reveal that, in the long term, national income and inflation exhibit positive yet insignificant effects, whereas exchange rates exert a considerable negative impact, and foreign exchange reserves yield a substantial positive effect. Interestingly, in the short term, national income, exchange rates, foreign exchange reserves, and inflation demonstrate no discernible impact on Indonesia's imports of capital goods.